Gestión financiera de los ingresos y gastos en la Empresa Lubrispa de la ciudad de Babahoyo en el período 2023. - Yance González, Evelyn Jomaira (2024)
In this investigation we will analyze the financial management of income and expenses during the period 2023 compared to previous years, observing that a problem arose in their income which caused fluctuations in their income statement in order to learn a little more about the situation. that the company LUBRISPA goes through, we conducted an interview with Mr. Juan Carlos Barrionuevo Nuñez, owner of the company, who provided us with the necessary information to carry out this project where a comparison of the income statements is made, for which we will carry out a horizontal and vertical analysis. , which allows us to see in more depth the variations of these periods. The main objective of this case study is to evaluate the financial management of the LUBRISPA company. On the other hand, we will use the deductive and inductive methods, which are what helped us both in collecting the information and in interpreting the results obtained, each one The results obtained will allow us to have a better perspective of the current situation of the company. Finally, each of the information obtained will be of great help so that they can face the problems that have arisen throughout the period.